가산자료모형을 이용한 서해 태안군 유어객의 편익추정 - 최종두; Jong Du Choi (자원·환경경제연구, 2014)
본 연구는 서해에 위치한 태안군을 방문하는 유어객의 방문 편익을 분석하기 위하여 개별여행비용법과 가산자료모형을 이용하여 수요모형을 추정하고 경제적 가치를 측정하였다. 여행객방문속성을 감안하여 분석모형으로 포아송모형(Poisson Model, PM), 음이항모형(Negative Binomial, NB), 절단된 포아송모형(Truncated Poisson Model, TPM), 절단된 음이항모형(Truncated Negative Binomial, TNB)을 분석에 이용하였다. 분석결과 추정계수들은 통계적으로 유의하게 나타났으며, 경제이론에도 부합되는 결과를 도출하였다. 과산포(overdispersion)현상은 발견되지 않았으며, 모형적합도검정을 통하여 절단된 포아송모형이 적정모형으로 선정되었다. 또한, 서해 태안군 해역내 유어활동의 경제적 가치를 추정하기 위하여 유어객의 연평균 출조횟수와 최적모형으로 선정된 절단된 포아송모형(TPM)으로 분석한 결과 1인 1회 출조당 경제적 가치는 254,453원이며, 1인당 연간 총 경제적 가치는 1,536,896원으로 도출되었다. The purpose of this study is to estimate the economic value of the recreational sea fishing in the Yellow Sea using count data model. For estimating consumer surplus, we used several count data model of travel cost recreation demand such as a poisson model(PM), a negative binomial model(NBM), a truncated poisson model(TPM), and a truncated negative binomial model(TNBM). Model results show that there is no exist the over-dispersion problem and a NBM was statistically more suitable than the other models. All parameters estimated are statistically significant and theoretically valid. The NBM was applied to estimate the travel demand and consumer surplus. The consumer surplus pre trip was estimated to be 254,453won, total consumer surplus per person and per year 1,536,896won.